Intervention To Address Childhood Undernutrition: A Systematic Review - Eric Chee How Tan; Marilyn Maluda; Mohd Yusof Ibrahim; Kai Joo Lim; Aza Sherin Mohd Yusuff; Khamisah Awang Lukman (University Malaysia Sabah, 2024)
Introduction: Childhood undernutrition while being a preventable condition remains a major public health issue because it contributes to the mortality and morbidity of children globally. Intervention strategies to improve the nutritional status of children include therapeutic food, cash transfers, antibiotics and nutritional education. The objective is to review the effects of various nutritional interventions in addressing undernutrition in children.